The miR396-GRFs Module Mediates the Prevention of Photo-oxidative Damage by Brassinosteroids during Seedling De-Etiolation in Arabidopsis. Issue 8 (2nd June 2020) - Wang, Lingyan; Tian, Yanchen; Shi, Wen; Yu, Ping; Hu, Yanfei; Lv, Jinyang; Fu, Chunxiang; Fan, Min; Bai, Ming-Yi
Abstract : BRs play important roles in the transition from skotomorphogenesis to photomorphogenesis by optimizing the biosynthesis of chlorophyll through the BZR1-PIF4-GRF7 transcriptional complex. Abstract: The switch from dark- to light-mediated development is critical for the survival and growth of seedlings, but the underlying regulatory mechanisms are incomplete. Here, we show that the steroids phytohormone brassinosteroids play crucial roles during this developmental transition by regulating chlorophyll biosynthesis to promote greening of etiolated seedlings upon light exposure. Etiolated seedlings of the brassinosteroids-deficient det2-1 ( de-etiolated2 ) mutant accumulated excess protochlorophyllide, resulting in photo-oxidative damage upon exposure to light. Conversely, the gain-of-function mutant bzr1-1D ( brassinazole-resistant 1-1D ) suppressed the protochlorophyllide accumulation of det2-1, thereby promoting greening of etiolated seedlings. Genetic analysis indicated that phytochrome-interacting factors (PIFs) were required for BZR1-mediated seedling greening. Furthermore, we reveal that GROWTH REGULATING FACTOR 7 ( GRF7 ) and GRF8 are induced by BZR1 and PIF4 to repress chlorophyll biosynthesis and promote seedling greening. Suppression of GRFs function by overexpressing microRNA396a caused an accumulation of protochlorophyllide in the dark and severe photobleaching upon light exposure. Additionally, BZR1, PIF4, and GRF7 interact with each other and precisely regulate the expression of chlorophyll biosynthetic genes. Our findings reveal an essential role for BRs in promoting seedling development and survival during the initial emergence of seedlings from subterranean darkness into sunlight.